(untitled) (Papeles, 2023)
Introduction: This study aimed to analyze the distance teaching of Geography in Venezuelan general secondary education in the framework of the covid-19 pandemic based on the perception of the students of the San Antonio de Padua Private Educational Unit. Methodology: The methodology used is based on the lines of the quantitative approach, being a descriptive research with a non-experimental and field design. For the collection of information, a Likert-type questionnaire was used based on the areas of attention for distance education proposed by Cubillán and Labarca (2021), which was applied to the 4th and 5th year students of the institution under study. Results and Discussion: Among the results, it stands out that more than 45 % of the students assure that the distance classes of Geography were based on the sending of activities to be carried out; 65.6 % indicated that the most used technological tools were WhatsApp and Telegram; and 53.1 % assert that the teacher did not use Geography tools such as Google Maps to develop content. Conclusions: It is concluded that in the pedagogical area, Geography teachers dedicated themselves to making a copy of face-to-face education through virtuality; in the technological area, they turned to digital tools not specific to the area; In the area of educational design, teachers did not design Geography-specific activities using appropriate technology; and in the research area, technology was not used to create content but to memorize concepts.